2012
DOI: 10.1007/s10900-012-9579-3
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Rural Women: Breast Cancer Prevention Information Seeking Behaviors and Interest in Internet, Cell Phone, and Text Use

Abstract: The purpose of this study was to examine the breast cancer prevention information seeking behaviors among rural women, the prevalence of Internet, cell, and text use, and interest to receive breast cancer prevention information cell and text messages. While growing literature for breast cancer information sources supports the use of the Internet, little is known about breast cancer prevention information seeking behaviors among rural women and mobile technology. Using a cross-sectional study design, data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Studies among young, urban African Americans, rural whites, and Hispanic women demonstrated interest in receiving information about health issues (including breast cancer) via text messaging or cell phone. 8789 Data on technology adoption by minority populations suggest that this avenue must be pursued to eliminate cancer health disparities.…”
Section: Tools For Cancer Prevention Researchmentioning
confidence: 99%
“…Studies among young, urban African Americans, rural whites, and Hispanic women demonstrated interest in receiving information about health issues (including breast cancer) via text messaging or cell phone. 8789 Data on technology adoption by minority populations suggest that this avenue must be pursued to eliminate cancer health disparities.…”
Section: Tools For Cancer Prevention Researchmentioning
confidence: 99%
“…For example, Eakin et al found that breast cancer survivors participating in their telephone-based exercise intervention were more likely to report interest in the same intervention being delivered face to face versus the Internet (83% vs 76%) [25]. Age has also been shown to be predictive of delivery preference [26] and use [27,28]. Increasingly, specific information is needed to understand cancer survivors’ preferences for intervention modalities in order to design programs that produce the greatest public health impact.…”
Section: Introductionmentioning
confidence: 99%
“…More efforts in this direction are urgently needed in Mexico. Mass media campaigns and the use of new communication technologies (E-Health) can be of great help to promote self-breast examinations and to remind women about the importance of periodically carrying out mammograms 39,40 . On the other hand, breast cancer programs should also integrate the provision of psychological support and postsurgical physical rehabilitation 41,42 to improve the patients' quality of life, as it is done in other countries.…”
Section: Discussionmentioning
confidence: 99%